Conjugate gradient algorithms in nonconvex optimization - Pytlak, Radosław (Springer, 2017)
This up-to-date book is on algorithms for large-scale unconstrained and bound constrained optimization. Optimization techniques are shown from a conjugate gradient algorithm perspective.